Hard carbon anodes derived from phenolic resin/sucrose cross‐linking network for high‐performance sodium‐ion batteries - Xu, Ran; Sun, Ning; Zhou, Huanyu; Chang, Xiaqing; Soomro, Razium A.; Xu, Bin (Battery energy, 2023)
Hard carbons are widely studied as anode materials for sodium‐ion batteries (SIBs) due to their high Na‐storage capacity, long cycle life, and low cost. However, the low initial coulombic efficiency (ICE) and poor cycle performance remain bottleneck concerns that necessitate a comprehensive material engineering solution. Herein, we propose a facile strategy to synthesize amorphous carbons with pseudo‐graphitic dominated crystalline, expanded interlayer spacing, and reduced surface defects via carbonization of the cross‐linking network of phenolic resin and sucrose. An elaborate structural and electrochemical characteristics analysis has been investigated against different sucrose contents and carbonization temperatures. The representative PF‐S‐55‐1200 with the optimum cross‐linking degree as well as carbonization temperature realizes a high reversible Na‐storage capacity of 323.0 mAh g−1 with an ICE as high as 86.4%, much superior to the pristine phenolic resin pyrolytic carbon with a capacity of 267.1 mAh g−1 and an ICE of 46.3%. The hybrid hard carbons also exhibit robust structural stability with a prolonged cycle lifespan evidenced by a retained capacity of 238.3 mAh g−1 at a current density of 200 mA g−1 over 1500 cycles. The proposed route promises low‐cost and high‐performance hybrid hard carbons with optimized structural configuration for advanced SIBs. Carbon heterostructure (PF‐S) with prominent pseudo‐graphitic regions and reduced surface defects has been successfully prepared from resin/sucrose cross‐linking networks. The representative PF‐S‐55‐1200 with the optimum cross‐linking degree realizes a high reversible Na‐storage capacity of 323.0 mAh g−1 with an initial coulombic efficiency (ICE) up to 86.4%, as well as excellent cycle and rate capability with no capacity decay over 1500 cycles.